KEEFEKTIFAN IMPLEMENTASI KURIKULUM 2013 PADA PEMBELAJARAN AKUNTAN-SI DI SMK NEGERI 1 KLATEN - Hastuti, Dwi; ., Sudiyanto; Sumaryati, Sri (Tata Arta : Jurnal Pendidikan Akuntansi, 2016)
ABSTRACTThe objectives of this research are to investigate: (1) the effectiveness of the learning planning in the 2013 curriculum implementation in the accounting learning; (2) the effectiveness of the learning pro-cess in the 2013 curriculum implementation in the accounting learning; and (3) the effectiveness of the learning result assessment in the 2013 curriculum implementation in the accounting learning. This re-search used the descriptive research method. Its population was all of the teachers and students of ac-counting expertise programs of vocational high schools of Klaten. Its samples were the teachers and stu-dents of accounting expertise program of state vocational high school 1 of Klaten. They were determined by using the purposive sampling technique. The data of learning planning, implementation, and assess-ment were collected through questionnaire, observation, and documentation. They were analyzed by us-ing the descriptive quantitative method. The results of research are as follows: Firstly, the 2013 curricu-lum implementation in the accounting learning planning is very effective with the score of 41.33. Sec-ondly, the 2013 curriculum implementation in the accounting learning process (implementation) is effec-tive with the score of 38.26. Finally, the 2013 curriculum implementation in the Accounting learning as-sessment is effective with the score of skor 35.Keywords: effectiveness 2013 curriculum, accounting learning, vocational high schoolABSTRAKPenelitian ini bertujuan untuk mengetahui (1) keefektifan perencanaan pembelajaran dalam imple-mentasi kurikulum 2013 pada pembelajaran akuntansi; (2) keefektifan pelaksanaan proses pembelajaran dalam implementasi kurikulum 2013 pada pembelajaran akuntansi; dan (3) keefektifan penilaian hasil belajar dalam implementasi kurikulum 2013 pada pembelajaran akuntansi. Populasi dalam penelitian ini adalah seluruh guru dan siswa di Sekolah Menengah Kejuruan paket keahlian akuntansi di Klaten. Sam-pel yang terpilih adalah guru dan siswa SMK N 1 Klaten dengan teknik pengambilan sampel purposive sampling. Penelitian ini menggunakan metode deskriptif. Pengumpulan data perencanaan, pelaksanaan dan penilaian pembelajaran dilaksanakan dengan teknik angket, observasi serta dokumentasi. Analisis data menggunakan analisis deskriptif kuantitatif. Hasil penelitian menunjukkan sebagai berikut ini. Per-tama, implementasi kurikulum 2013 pada bagian perencanaan pembelajaran akuntansi sudah pada krite-ria sangat efektif dengan skor 41,33. Kedua, implementasi kurikulum 2013 pada bagian pelaksanaan pembelajaran akuntansi sudah pada kriteria efektif dengan skor 38,26. Ketiga, implementasi kurikulum 2013 pada bagian penilaian pembelajaran akuntansi sudah pada kriteria efektif dengan skor 35.Kata Kunci : keefektifan kurikulum 2013, pembelajaran akuntansi, SMK